Apoptosis and other immune biomarkers predict influenza vaccine responsiveness. Issue 1 (16th April 2013) - Furman, David; Jojic, Vladimir; Kidd, Brian; Shen‐Orr, Shai; Price, Jordan; Jarrell, Justin; Tse, Tiffany; Huang, Huang; Lund, Peder; Maecker, Holden T; Utz, Paul J; Dekker, Cornelia L; et al.
Abstract : Despite the importance of the immune system in many diseases, there are currently no objective benchmarks of immunological health. In an effort to identifying such markers, we used influenza vaccination in 30 young (20–30 years) and 59 older subjects (60 to >89 years) as models for strong and weak immune responses, respectively, and assayed their serological responses to influenza strains as well as a wide variety of other parameters, including gene expression, antibodies to hemagglutinin peptides, serum cytokines, cell subset phenotypes and in vitro cytokine stimulation. Using machine learning, we identified nine variables that predict the antibody response with 84% accuracy. Two of these variables are involved in apoptosis, which positively associated with the response to vaccination and was confirmed to be a contributor to vaccine responsiveness in mice. The identification of these biomarkers provides new insights into what immune features may be most important for immune health. Abstract : A systems analysis of immune biomarkers in 89 young and older adults revealed age‐dependent and age‐independent features, including markers of apoptosis that correlated with antibody responses to a seasonal influenza vaccine. Synopsis: A systems analysis of immune biomarkers in 89 young and older adults revealed age‐dependent and age‐independent features, including markers of apoptosis that correlated with antibody responses to a seasonal influenza vaccine. Influenza hemagglutinin peptide arrays reveal age‐associated effects that correlate with both pre‐existing and vaccine‐induced antibody titers. Age‐dependent and age‐independent baseline immune parameters correlate with and substantially predict the serological response to a seasonal influenza vaccine. Soluble FasL and gene modules associated with apoptosis are predictors of the serological response to an influenza vaccine, which was abrogated in Fas‐deficient mice.